On-line legal and civic counseling for people with disabilities. Pandemic observations - Różycka, Aleksandra (Virtualizing the lives of people with disabilities, 2021)
The public service of citizens and legal advice has been virtualized even before the lockdown had been implemented in response to the pandemic. This was possible due to previous experiences and both legal and organizational changes introduced one year earlier, which enabled the provision of remote services for people with disabilities from the beginning of 2019. This group of citizens was initially given the choice between advice given in person and services provided by various means of distance communication. Later, in time of the pandemic, the remote advice in most of the poviats (regional unit in Poland) became the only one accessible to all the citizens. Thus people with disabilities lost additional conveniences consisting in the possibility of having a personal meeting both at the point of advice and place of residence, in a place provided with appropriate equipment supporting communication or offering an access to a sign language interpreter. This article attempts to answer the question whether, under these conditions, it is possible to fulfill the role of legal and citizens counseling, taking into account that the problems of the beneficiaries may be complex and they are quite distanced from the ideal of fair protection of rights and obligations contained in the legal system. It was also considered what circumstances and forms of remote counseling contribute to maintaining the appropriate social quality of counseling services, which seems to condition nearing the institutions of the legal system and applicable regulations to a specific situation of an individual and its entire context, and consequently increases the chance of receiving adequate and valuable legal or citizens advice by people with disabilities.